Pengaruh Gaya Hidup Islami, Halal Awareness, dan Korean Wave Terhadap Minat Beli Makanan Korea pada Gen Z Muslim di Kota Tangerang - Khoirunnisa Sabila; Yan Putra Timur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of Islamic lifestyle, halal awareness, and the Korean wave on purchase intention toward Makanan korea among Muslim Generation Z in Tangerang City. This research employs a quantitative method using primary data collected through questionnaire distribution. The sampling technique used is purposive sampling with a total of 105 Muslim Generation Z respondents domiciled in Tangerang City. The data were analyzed using multiple linear regression analysis. The results indicate that halal awareness and the Korean wave partially have a significant effect on purchase intention toward Makanan korea, while Islamic lifestyle does not have a significant effect. However, simultaneously, Islamic lifestyle, halal awareness, and the Korean wave have a significant effect on purchase intention toward Makanan korea among Muslim Generation Z in Tangerang City.